The Bidirectional Relationship between Rumination and Self-Esteem: Evidence from Longitudinal Tracking and Diary Methods - Li, Xiaowen; He, Yuanqing; Ye, Kaili; Xu, Hao (Studia psychologica, 2024)
Rumination and self-esteem are pivotal in mental health research. Existing studies indicate that there is an association between rumination and self-esteem, however, there is a lack of evidence for bidirectional influences. This study employed longitudinal and diary methods to investigate their bidirectional influences. The initial phase involved a two-wave survey, conducted over a year, with 1157 participants to examine the bidirectional predictive relationship between rumination and self-esteem. Cross-Lagged Panel Model (CLPM) indicated that baseline rumination could forecast subsequent self-esteem levels, and vice versa. To reduce recall bias, the second phase involved a 28-day diary study with 185 participants, revealing that daily fluctuations in rumination could predict the following day's self-esteem, and similarly, daily self-esteem levels could predict the next day's rumination. This research elucidates the bidirectional influences between rumination and self-esteem, introducing a bidirectional spiral ascension model. This model holds significant theoretical implications for mental health research.